Size Analysis of the Indus River Sands, West Pakistan - Tahirkheli, R. A. Khan (Journal of Himalayan Earth Sciences, 1968)
In this paper an auempt has been made to evaluate the grade of the Mud-sized material in the Indus alluvium between Kalabagh and Skardu. The most widely used satistical devices of quartile measures were applied to describe the sediments. Some of the results obtained a recomparable with those of similar work carried out by the authors in other part of the world.